Closed-loop supply chain models with product remanufacturing under random demand. (2nd January 2021) - Dong, Junfeng; Jiang, Li; Lu, Wenxing; Guo, Qiang
Abstract : This study addresses the problem of choosing the appropriate closed-loop supply chain structure for the collection of used products from customers under random demand. We consider a two-echelon supply chain with three decision-making structures: (1) the manufacturer who coordinates with the retailer to obtain optimal channel profit, (2) the manufacturer who collects used products directly from customers, and (3) the retailer who collects used products from customers and the manufacturer who pays a transfer price to reacquire the products. We show that a unique optimal solution exists when the collection cost function satisfies the specified conditions under different models. We also identify differences among the three models and provide managerial guidelines for various marketing environments and collection cost functions. Surprisingly, contrary to previous studies, we find that the collection rate is not always largest under a centrally coordinated system compared with other making structures. As a special case, we investigate the effect of the coefficient of collection effort cost when cost structure is given.